The Impacts of Coastal Reclamation to the Quality of Life of Tanjung Tokong Community, Penang - Nadzhirah Mohd Nadzir (Journal of Architecture, Planning and Construction Management, 2020)
Many studies had shown that coastal area serves the economic functions including supporting aquaculture activities, tourism, transportation, mining, communication and facilitating navigation. These activities resulted in rapid population growth within the coastal areas. A coastal reclamation becomes one of the solutions to overcome the growing population in the coastal area. However, coastal reclamation might have positive and negative impacts to the employment and income of the existing community who are depending on the economic resources of the coastal areas. This paper presents the impacts of coastal reclamation to the community in Tanjung Tokong, Penang which focuses on the aspects of employment and income. It draws literatures from various local and international publications and also from government reports and publications. The data were collected through questionnaire survey and interview. Additionally, the survey questionnaire was analyzed using Statistical Package for Social Science (SPSS). The results show that there are changes in type of profession and difference in mean of salary before and after the reclamation, however statistically there is no significant difference. The findings also suggested that only a minority community involve in profession shifting. As a result, it is recommended that community should take advantage from the coastal reclamation development in terms of tourism and employment provided by the developer as coastal area has a unique character.